Some Generalized Formulas of Hadamard-Type Fractional Integral Inequalities. (8th June 2022) - Zhang, Xiujun; Farid, Ghulam; Yasmeen, Hafsa; Nonlaopon, Kamsing
Abstract : This paper is aimed at establishing the generalized forms of Riemann-Liouville fractional inequalities of the Hadamard type for a class of functions known as strongly exponentially α, h − m -p -convex functions. These inequalities provide some general formulas from which one can get associated inequalities for various types of exponentially convex and strongly convex functions. Refinements of well-known inequalities are also deducible from the established theorems.